2013
DOI: 10.1074/jbc.r112.420752
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Calcium Uniporter (MCU): Molecular Identity and Physiological Roles

Abstract: The direct measurement of mitochondrial [Ca 2؉ ] with highly specific probes demonstrated that major swings in organellar [Ca 2؉ ] parallel the changes occurring in the cytosol and regulate processes as diverse as aerobic metabolism and cell death by necrosis and apoptosis. Despite great biological relevance, insight was limited by the complete lack of molecular understanding. The situation has changed, and new perspectives have emerged following the very recent identification of the mitochondrial Ca 2؉ un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(110 citation statements)
references
References 87 publications
6
98
0
6
Order By: Relevance
“…Ca 2+ uptake from the mitochondrial intermembrane space into the mitochondrial matrix occurs predominantly through the MCU complex containing the Ca 2+ selective ion channel MCU (Mitochondrial Calcium Uniporter) [49,50] and several accessory proteins [51][52][53][54]. Recalling that OPA1 knockdown increases the diffusibility of cytochrome c through the crista junctions [38,45,46] we postulated that if significant Ca 2+ uptake into the matrix occurs from the lumen of the cristae, reduced expression of Opa1 would increase the access of Ca 2+ to the transporters in the crista membrane and consequently would enhance Ca 2+ uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ uptake from the mitochondrial intermembrane space into the mitochondrial matrix occurs predominantly through the MCU complex containing the Ca 2+ selective ion channel MCU (Mitochondrial Calcium Uniporter) [49,50] and several accessory proteins [51][52][53][54]. Recalling that OPA1 knockdown increases the diffusibility of cytochrome c through the crista junctions [38,45,46] we postulated that if significant Ca 2+ uptake into the matrix occurs from the lumen of the cristae, reduced expression of Opa1 would increase the access of Ca 2+ to the transporters in the crista membrane and consequently would enhance Ca 2+ uptake.…”
Section: Discussionmentioning
confidence: 99%
“…P < 0.05 (Student's t test). n ¼ 4-6 decrease in membrane potential, and consequently loss of mitochondrial functions and cell death (Patron et al 2013). Ca 2+ fluctuations may interfere in lysosomal homeostasis, which interfere in a variety of mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In somatic cells, mitochondrial calcium uptake is undertaken by a mitochondrial calcium uniporter (MCU; Fig. 2) and is known to control intracellular calcium signals, cell metabolism and cell survival (for recent reviews, see Rizzuto et al (2012) and Patron et al (2013)). Proteomic data have confirmed that human sperm do possess MCU, as well as MCU regulator 1 , Wang et al 2013.…”
Section: C Signallingmentioning
confidence: 99%